Pengaruh interactivity dan vividness dalam augmented reality terhadap minat beli produk kecantikan di e-commerce - Millenia, Shinta; Tjokrosaputro, Miharni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
This study aims to examine the influence of Augmented Reality (AR) in terms of interactivity and vividness regarding its ability to realistically depict virtual products into real-world visuals, in affecting consumer purchase intention toward beauty products. The theoretical foundation of this research is the Technology Acceptance Model. The data analysis method used in this study is Structural Equation Modeling (SEM). This is a quantitative study with data collected cross-sectionally through a survey using a questionnaire, and the data were processed using the SmartPLS software. In addition, this study employs non-probability sampling with a purposive sampling technique, as samples were selected based on predetermined criteria. The results show that AR interactivity and vividness have a positive and significant effect on purchase intention of beauty products in e-commerce. Based on these findings, the study indicates that the use of augmented reality technology in e-commerce for beauty products can assist consumers in making purchase decisions.